Efficacy and Safety of Interferon Beta-1b in the Management of Patients with COVID-19: A Prospective, Open-Label, Non-Randomized Trial - Nima Rouhani; Elahe Karimpour-razkenari; Mostafa Alizadeh Forutan; Monireh Ghazaeian; Ebrahim Salehifar; Mohammad Sadegh Rezai; Sahar Fallah (Journal of Pharmaceutical Care, 2021)
Backgrounds: There is no proven therapy for coronavirus disease 2019 (COVID-19) so far. The aim of this study was to evaluate the effect of interferon beta-1b combined with lopinavir/ritonavir and hydroxychloroquine in managing COVID-19.Methods: This is a non-randomized, open-label study on adult patients with moderate to severe COVID-19. The patients (≥ 18 years) received hydroxychloroquine 400 mg single dose, and lopinavir 400 mg/ritonavir 100 mg every 12 h (for 7-10 days) with or without subcutaneous interferon (IFN) beta-1b 250 mcg every other day for e primary outcome was clinical improvement in NEWS2 changes. Duration of hospital stay, mortality rate, and safety profile of therapeutic regimens were secondary outcomes.Results: Between March 20 and April 3, 2020, a total of 114 patients were recruited and 59 patients completed the study. The IFN group had a significant improvement in clinical symptoms due to a significant reduction in NEWS2 (83.3% (25) vs 48.3% (14), P= 0.004). The time to clinical response in the IFN group was shorter than the control group (7 (5-12) days vs 9.5 (7-18), P=0.037). The IFN group also showed a significantly lower rate of 28-day mortality (6.8% (2) vs 34.5% (10), P= 0.01) and a lower need for invasive ventilation (6.8% (2) vs 34.5 (10), P= 0.008). Although the duration of ICU stay was marginally shorter in the IFN group, the results were not significantly different between the two groups (P=0.06).Conclusion: IFN beta-1b could be a potential therapeutic option for patients with moderate to severe COVID-19.